Digital Heritage Knowledge Governance for Islamic Higher Education: A Stakeholder-Oriented WebGIS for Historic Mosques in Central Java - Emawati Emawati; Bimo Haryo Setyoko (Universitas Nurul Jadid, 2025)
Historic mosques carry valuable Islamic cultural knowledge, but their historical, architectural, and spatial records often stay scattered across separate sources. This condition weakens the ability of educational and heritage stakeholders to organize and reach that knowledge. This study developed a stakeholder-oriented WebGIS for the digital heritage knowledge governance of historic mosques in Central Java. It applied Research and Development through the Design Science Research Methodology, moving from needs assessment, field observation, and GPS-based mapping to system development, implementation, and user evaluation. Data were examined descriptively using frequencies, percentages, field verification, and functional assessment. Historical information was the content most respondents wanted, chosen by four of six participants, while five of six regarded interactive mapping as important or very important, and easy navigation ranked as the leading function. The resulting WebGIS joined hierarchical geographic navigation with historical, architectural, and visual records, and an AI-assisted feature was integrated as a supporting analytical layer. Preliminary users reported no negative assessments, though most ratings stayed moderately positive. These results imply that a mosque WebGIS can serve educational institutions as knowledge-governance infrastructure that strengthens heritage information management and widens access to Islamic cultural knowledge.